Helicobacter pylori-Induced HB-EGF Upregulates Gastrin Expression via the EGF Receptor, C-Raf, Mek1, and Erk2 in the MAPK Pathway - Gunawardhana, Niluka; Jang, Sungil; Choi, Yun Hui; Hong, Youngmin A.; Jeon, Yeong-Eui; Kim, Aeryun; Su, Hanfu; Kim, Ji-Hye; Yoo, Yun-Jung; Merrell, D. Scott; Kim, Jinmoon; Cha, Jeong-Heon (Frontiers in Cellular and Infection Microbiology, 2018)
Helicobacter pylori is associated with hypergastrinemia, which has been linked to the development of gastric diseases. Although the molecular mechanism is not fully understood, H. pylori is known to modulate the Erk pathway for induction of gastrin expression. Herein we found that an epidermal growth factor (EGF) receptor kinase inhibitor significantly blocked H. pylori-induced gastrin promoter activity, suggesting involvement of EGF receptor ligands. Indeed, H. pylori induced mRNA expression of EGF family members such as amphiregulin, EGF, heparin-binding EGF-like growth factor (HB-EGF), and transforming growth factor-. Of these, specific siRNA targeting of HB-EGF significantly blocked H. pylori-induced gastrin expression. Moreover, H. pylori induced HB-EGF ectodomain shedding, which we found to be a critical process for H. pylori-induced gastrin expression. Thus, we demonstrate a novel role for human mature HB-EGF in stimulating gastrin promoter activity during H. pylori infection. Further investigation using specific siRNAs targeting each isoform of Raf, Mek and Erk elucidated that the mechanism underlying H. pylori-induced gastrin expression can be delineated as the sequential activation of HB-EGF, the EGF receptor, C-Raf, Mek1 and the Erk2 molecules in the MAPK pathway. Surprisingly, whereas Erk2 acts as a potent activator of gastrin expression, siRNA knockdown of Erk1 induced gastrin promoter activity, suggesting that Erk1 typically acts as a repressor of gastrin expression. Elucidation of the mechanism of gastrin modulation by HB-EGF-mediated EGF receptor transactivation should facilitate the development of therapeutic strategies against H. pylori-related hypergastrinemia and consequently gastric disease development, including gastric cancers.